Pathogenesis, Clinic and Principles of Treatment of Burn Shock (Eurasian Research Bulletin, 2022)
The main questions concerning pathogenesis, clinical diagnostics and principles of treatment of burn shock are consecrated in the article. It is proved that the introduction of the principles of emergency anti-shock therapy burned at the prehospital stage and complex treatment with the use of refortan or stabilazole facilitates the course of shock, reduces mortality in patients with critical and supercritical burns.